2021
DOI: 10.1038/s41467-021-22389-5
|View full text |Cite
|
Sign up to set email alerts
|

ATP6V0A1 encoding the a1-subunit of the V0 domain of vacuolar H+-ATPases is essential for brain development in humans and mice

Abstract: Vacuolar H+-ATPases (V-ATPases) transport protons across cellular membranes to acidify various organelles. ATP6V0A1 encodes the a1-subunit of the V0 domain of V-ATPases, which is strongly expressed in neurons. However, its role in brain development is unknown. Here we report four individuals with developmental and epileptic encephalopathy with ATP6V0A1 variants: two individuals with a de novo missense variant (R741Q) and the other two individuals with biallelic variants comprising one almost complete loss-of-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
48
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 37 publications
2
48
0
Order By: Relevance
“…These findings corroborate recent reports indicating that in Drosophila the V-ATPase-mediated acidification of the endolysosomal compartment is required for the activation of Notch in endosomes (Sorensen & Conner, 2010) and expression of a dominant negative subunit of V-ATPase in neural precursors reduced Notch signaling and depleted neural stem cells leading to neuronal differentiation (Lange et al, 2011). The severe impairment of the autophagic machinery upon knock down of the ATP6V0A1 ortholog in C. elegans, and the reduced protein clearance by lysosomes upon introduction of the R740Q variant in homozygote state reported here, together with the recent description of severe impairment of the lysosomal dysfunction and decreased Cathepsin D activity in homozygous mutant mice harbouring the human R741Q and A512P variants (Aoto et al, 2021), recapitulate the results observed in neuronal cell lines upon overexpression of the R740Q variant, supporting an antimorphic mode of action of the R740Q and the other de novo variants.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…These findings corroborate recent reports indicating that in Drosophila the V-ATPase-mediated acidification of the endolysosomal compartment is required for the activation of Notch in endosomes (Sorensen & Conner, 2010) and expression of a dominant negative subunit of V-ATPase in neural precursors reduced Notch signaling and depleted neural stem cells leading to neuronal differentiation (Lange et al, 2011). The severe impairment of the autophagic machinery upon knock down of the ATP6V0A1 ortholog in C. elegans, and the reduced protein clearance by lysosomes upon introduction of the R740Q variant in homozygote state reported here, together with the recent description of severe impairment of the lysosomal dysfunction and decreased Cathepsin D activity in homozygous mutant mice harbouring the human R741Q and A512P variants (Aoto et al, 2021), recapitulate the results observed in neuronal cell lines upon overexpression of the R740Q variant, supporting an antimorphic mode of action of the R740Q and the other de novo variants.…”
Section: Discussionsupporting
confidence: 65%
“…Recently, Aoto et al identified two subjects with intellectual disability and epilepsy carrying a de novo missense R741Q substitution in ATP6V0A1 and two with biallelic variants, comprising one complete loss of function and the A512P or N534D missense variant (Aoto et al, 2021), respectively corresponding to R740Q, A505P and N527D in the updated accession number NM_001130021.3 used in this manuscript. Here we report 17 subjects from 14 unrelated families carrying the R740Q, other newly identified de novo missense or inherited biallelic variants in this gene, representing the largest cohort of ATP6V0A1associated disease mutations to date.…”
Section: Discussionmentioning
confidence: 99%
“…3 , Additional file 1 : Table S2 ). V-ATPase is required for synaptic vesicle exocytosis [ 41 ] The a1-subunit of the V0 domain in ATP6V0A1 was recently shown to be highly expressed in neurons and to be essential for human brain development [ 42 , 43 ]. In another example, NEASE identified two co-regulated events of the genes CLTA and CLTB (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…NEASE also provides a detailed view on the affected mechanisms, such as an exon skipping event in the gene ATP6V0A1 overlapping with the V_ATPase_I domain (PFAM id: PF01496) and affecting the binding with seven other proteins from the complex vacuolar ATPase (V-ATPase) (p-value: 7.14e-17, Figure 3, Additional files 1: Table S2). V-ATPase is required for synaptic vesicle exocytosis [37] The a1-subunit of the V0 domain in ATP6V0A1 was recently shown to be highly expressed in neurons and to be essential for human brain development [38,39]. In another example, NEASE identified two co-regulated events of the genes CLTA and CLTB (Figure 3).…”
Section: Resultsmentioning
confidence: 99%